Isothermal and non-isothermal oil–water flow and viscous fingering in a porous medium - Sheorey, Tanuja; Muralidhar, K. (International journal of thermal sciences, 2003)
Immiscible flow of heavy oil in a porous formation by high temperature pressurized water has been numerically studied. The physical region is a square domain in the horizontal plane with low and high pressure points at the opposite corners along one of the diagonals. Water, the invading fluid, when introduced at high pressure displaces the in situ oil towards the low pressure production zone. The extent of displacement of oil by water through the porous medium in a given amount of time and the appearance of preferential flow paths ( fingers) is the subject of the present investigation. The resistance to water–oil movement arises from the viscous forces in the fluid phases and the capillary force at their interface. Based on their relative magnitudes, various forms of displacement mechanisms can be realized. As the viscosity ratio of heavy oil to water is large, viscous forces in the oil phase become dominant and constitute the major factor for controlling the flow distortions in the porous formation. A mathematical model that can treat the individual fluid pressures, capillary effects and heat transfer has been employed in the present work. A fully implicit, two-dimensional numerical model has been used to compute the pressure and temperature fields. The domain decomposition technique has been adopted in the numerical solution since the problem is computationally intensive. Naturally occurring oil-rich reservoirs to which the present study is applicable are inhomogeneous and layered. A qualitative study has been carried out to explore the effect of permeability variations on the flow patterns. Numerical calculations show that non-isothermal effects as well as layering promote the formation of viscous fingers and consequently the sweep efficiency of the high pressure water front.